Temperature dependent elastic, lattice vibronic and thermal properties of nanomaterials - Gu, Mingxia (2009)
It is well known that the physical properties of a macroscopic system can be well described using classical approaches such as the Gibbs free energy or the continuum medium mechanics, which relates the measurable quantities directly to the external applied stimulus such as temperature, pressure, chemical composition, electric and magnetic field, etc, without considering the atomistic origin. At atomic scale, quantum effect becomes dominant and the physical properties of a small object can be reliably obtained from computations by solving the Schrödinger equations or Newton motion equations with a sum of averaged interatomic potentials as a key element. However, for a small system in nanometer scale, both classical and quantum approaches have their limitations. Therefore, an effective approach solving the difficulties encountered